Knowledge and readiness factors of food based logistics service providers towards halal practices in Malaysia - Kamarulzaman, Nitty Hirawaty; Abd Rahman, Azmawani; Ahmad Tarmizi, Hazwani; Abd Latif, Ismail (Universiti Putra Malaysia Press, 2018)
Malaysian consumers mainly associate the Halal logo as a certification for food safety. Food safety is one of the most pressing concerns for governments, consumers, and food chain players across the globe. The food safety certification processes and assurance guidelines like the Halal logo, Hazard Analysis Critical Control Point (HACCP), and Good Manufacturing Practices (GAP) are developed as consumer reassurance mechanisms. Specifically, the establishment of a Halal supply chain for food products is essential to provide 100% Halal quality end-products to consumers. The Halal supply chain is important to ensure the integrity of such products and services in fulfilling necessary religious obligations to Muslim end-consumers. To deliver halalan toyibban products to consumers, food-based logistics service providers (LSPs) need to comply with certain guidelines. However, different Halal guidelines and best practices of Halal logistics activities across the world may result in difficulties among food-based LSPs. This necessitates the development of standardized guidelines, regulations and best practices for Halal logistics, to preserve the religious integrity across this unique supply chain.